RESOLVING PLANT DAMAGE DISPUTES: AN ISLAMIC LAW PERSPECTIVE IN NAGARI SIMARASOK - Yani, Suci Fitri; Zulkifli, Zulkifli; Emrizal, Emrizal; Effendi, Amri (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
The primary issue in this research is the refusal of tree owners—whose pine and coconut trees have fallen, damaging neighboring houses and gardens—to provide compensation, leading to financial losses and disputes between the parties involved. This study aims to explore and describe the dispute resolution mechanism for compensation related to residents’ plants that damage others' property rights in Nagari Simarasok, Baso District, Agam Regency. Additionally, it examines the perspective of Islamic law on resolving such disputes.This qualitative, descriptive field research gathered data through interviews with four disputing parties, two Ninik Mamak (customary leaders), and community and religious leaders.The findings reveal that compensation disputes in Nagari Simarasok are resolved through agreements between the parties, facilitated by Ninik Mamak. The process involves deliberation, barundiang or baruumbuak, conducted at the property owner's house. Compensation is calculated by assessing all the damaged plants, and payments are often made in installments.From an Islamic law perspective, the dispute resolution mechanism aligns with peaceful settlement principles (al-sulh), mediation, and arbitration (tahkim). However, in some cases, the method used by Ninik Mamak to calculate compensation—by counting all the plants rather than assessing the actual damage—contradicts Islamic principles. Islamic law emphasizes fair valuation to ensure no party is harmed. Compensation payments should be neither excessive nor insufficient, adhering to the principles of justice and benefit (maslahah).